DNA bending mediated by ORC is essential for replication licensing in budding yeast - Wai Hei Lam; Daqi Yu; Qiongdan Zhang; Yuhan Lin; Ningning Li; Jian Li; Yue Wu; Yingyi Zhang; Ning Gao; Bik Kwoon Tye; Yuanliang Zhai; Shangyu Dang (Proceedings of the National Academy of Sciences, 2025)
In eukaryotes, the origin recognition complex (ORC) promotes the assembly of minichromosome maintenance 2 to 7 complexes into a head-to-head double hexamer at origin DNA in a process known as replication licensing. In this study, we present a series of cryoelectron microscopy structures of yeast ORC mutants in complex with origin DNA. We show that Orc6, the smallest subunit of ORC, utilizes its transcription factor II B-B domain to orchestrate the sequential binding of ORC to origin DNA. In addition, Orc6 plays the role of a scaffold by stabilizing the basic patch (BP) of Orc5 for ORC to capture and bend origin DNA. Importantly, disrupting DNA bending through mutating three key residues in Orc5-BP impairs ORC’s ability to promote replication initiation at two points during the pre-RC assembly process. This study dissects the multifaceted role of Orc6 in orchestrating ORC’s activities on DNA and underscores the vital role of DNA bending by ORC in replication licensing.